Exploring the Relationship between Media Literacy and Political Engagement - Bano, Syeda Ammarah; Mubbsher, Sofia; Zaheer, Lubna (Annals of Human and Social Sciences, 2024)
This study aims to investigate the relationship between media literacy and political engagement, addressing assumptions and concerns regarding their association. While scholars and educators anticipate a positive correlation between media education and prosocial objectives like political and civic engagement, empirical evidence supporting this link remains limited. Cross-sectional design employs survey method to collect data from sample of 357 university students. Multistage sampling techniques are utilized to ensure representativeness. Valid and reliable survey instruments assess participants’ levels of media literacy and their engagement with political activities. The findings reveal significant relationships between news media literacy and key measures of political engagement: political activities, current events knowledge and internal political efficacy. Additionally, certain dimensions of news media literacy are associated with lower levels of political trust among participants. The study recommends integrating comprehensive media literacy programs in university curricula to enhance political engagement. Further research should explore these dynamics across different populations.